2012
DOI: 10.1371/journal.pntd.0001522
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and Genetic Data Supporting the Transmission of Ancylostoma ceylanicum among Human and Domestic Animals

Abstract: BackgroundCurrently, information on species-specific hookworm infection is unavailable in Malaysia and is restricted worldwide due to limited application of molecular diagnostic tools. Given the importance of accurate identification of hookworms, this study was conducted as part of an ongoing molecular epidemiological investigation aimed at providing the first documented data on species-specific hookworm infection, associated risk factors and the role of domestic animals as reservoirs for hookworm infections i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
150
3
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(167 citation statements)
references
References 36 publications
6
150
3
8
Order By: Relevance
“…In many other studies, lack of footwear in association with the presence of free-roaming dogs provide a strong predictor for STH infections, particularly hookworm. 33,34 Moreover, more studies are reporting on the zoonotic ancylostomiasis caused by A. ceylanicum in humans in endemic areas in Southeast Asia. 23,[34][35][36] A recent genetic study to provide further evidence on zoonotic transmission of A. ceylanicum between humans and animals in Malaysia showed that some of the A. ceylanicum strains from both the human and animal host in the same geographical location are clustered together within the same group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many other studies, lack of footwear in association with the presence of free-roaming dogs provide a strong predictor for STH infections, particularly hookworm. 33,34 Moreover, more studies are reporting on the zoonotic ancylostomiasis caused by A. ceylanicum in humans in endemic areas in Southeast Asia. 23,[34][35][36] A recent genetic study to provide further evidence on zoonotic transmission of A. ceylanicum between humans and animals in Malaysia showed that some of the A. ceylanicum strains from both the human and animal host in the same geographical location are clustered together within the same group.…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirmed the previous epidemiological survey indicating that individuals who had close contact with dogs were more likely to be infected with A. ceylanicum. [33][34][35] Although the notion of zoonotic transmission of A. lumbricoides and T. trichiura between humans and dogs is still largely unclear, these animals may act as significant mechanical transmitter of ascariasis in the human population especially in communities where the habit of indiscriminate defecation exist. Molecular-based tool studies have shown that dogs act as disseminators and environmental contaminators of A. lumbricoides in communities where indiscriminate defecation is common.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Ancylostoma ceylanicum is now the second most common hookworm species infecting humans in Asia and possible cause of cutaneous larvae migrans or abdominal symptoms in infected patients, with reported high egg-positivity rates in Thailand, Laos, Cambodia, and Malaysia. [6][7][8][9][10] National surveys on the prevalence of soil-transmitted helminths (STHs) in Myanmar reported a reduction in hookworm prevalence in schoolchildren from 6.5% to 0.3% 7 years after a national deworming program. 11,12 A diagnosis of hookworm infection was usually made by microscopic examination of eggs or larvae in the fecal samples.…”
mentioning
confidence: 99%
“…Necator americanus is the most prevalent species of hookworm, whereas A. duodenale occurs in more geographically restricted areas . Ancylostoma ceylanicum is considered as a zoonotic species (Fujiwara et al 2006), but can cause patent infection in humans (Ngui et al 2012). Other species like Ancylostoma caninum and Ancylostoma brasiliense cause eosinophilic enteritis and cutaneous larva migrans syndrome and also cause zoonoses (Fujiwara et al 2006).…”
Section: Introductionmentioning
confidence: 99%